A randomised controlled trial of matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDITOF-MS) versus conventional microbiological methods for identifying pathogens: Impact on optimal antimicrobial therapy of invasive bacterial and fungal infections in Vietnam. Issue 6 (June 2019) - Nadjm, Behzad; Dat, Vu Quoc; Campbell, James I.; Dung, Vu Tien Viet; Torre, Alessandro; Tu, Nguyen Thi Cam; Van, Ninh Thi Thanh; Trinh, Dao Tuyet; Lan, Nguyen Phu Huong; Trung, Nguyen Vu; Hang, Nguyen Thi Thuy; Hoi, Le Thi; et al.
Highlights: MALDITOF MS provided more rapid identification of invasive bacterial and fungal pathogens than conventional microbiology. MALDITOF MS did not increase the proportion of patients on optimal therapy at 24 or 48 hours after positive culture. MALDITOF MS did not increase the proportion of patients receiving adequate therapy at 24 hours after positive culture. The most common reason for therapy being sub-optimal was use of overly broad spectrum or unnecessary multiple antibiotics. Summary: Objectives: We assessed the impact of MALDITOF-MS on the timeliness of optimal antimicrobial therapy through a parallel-arm randomised controlled trial in two hospitals in Vietnam. Methods: We recruited patients with a pathogen (bacterial or fungal) cultured from a normally sterile sample. Samples were randomly assigned (1:1) to identification by MALDITOF-MS or conventional diagnostics. The primary outcome was the proportion on optimal antimicrobial therapy within 24 h of positive culture, determined by a blinded independent review committee. Trial registered at ClinicalTrials.gov (NCT02306330). Results: Among 1005 randomised patients, pathogens were isolated from 628 (326 intervention, 302 control), with 377 excluded as likely contaminants or discharged/died before positive culture. Most isolates were cultured from blood (421/628, 67.0%). The proportion receiving optimal antimicrobial therapy within 24 h (the primary outcome) or 48 h of growth was not significantly different between MALDITOF-MS and control arms (135/326, 41.4% vs 120/302, 39.7%; Adjusted Odds ration (AOR) 1.17, p  = 0.40 and 151/326, 46.3% vs 141/302, 46.7%; AOR 1.05 p  = 0.79, respectively). Conclusions: MALDITOF-MS, in the absence of an antimicrobial stewardship programme, did not improve the proportion on optimal antimicrobial therapy at 24 or 48 h after first growth in a lower-middle income setting with high rates of antibiotic resistance.